Jaiveer Roy - Vohra, Neharika, 1966-; Mendonca, Valerie; Bajwa, Tanveer; Chari, Vijayalaxmi (London : Indian Institute of Management, Ahmedabad, 2020)
This case highlights issues in people management, especially support for people selected for leadership positions, and examines the performance indicators of an individual's performance at a broader level. It suggests that one of the mistakes managers sometimes make is driving conventional performance numbers, such as sales, etc., and not appreciating the softer aspects of performance. The role of leadership support in the performance of even the best employees is clearly highlighted. The case also points toward the mistakes or errors leaders may commit vis-a-vis their own role as a leader and mentor. The contribution of organizational factors such as not following processes and growing too fast is also highlighted.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Leadership -- Case studies